Dollars, DALYs and Decisions - Economic Aspects of the Mental Health System : Nonserial Publication. - Chisholm, Dan (World Health Organization, 2006)
The widening recognition of mental health as a significant international public health issue has led to an increasing need to demonstrate that investment of resources into service development is both required and also worthwhile. In particular, there is a need to generate evidence on mental health care strategies that are not only effective and appropriate but are also cost-effective and sustainable. Aimed at health policy-makers and service researchers with an interest in strengthening mental health systems, this publication sets out to highlight the need for and relevance of an economic dime.